2019
DOI: 10.1021/acs.molpharmaceut.9b00797
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Lipid Polymer Nanoparticles for Combined Chemo- and Photodynamic Therapy

Abstract: Retinoblastoma is a malignant tumor of the retina in infants. Conventional therapies are associated to severe side effects and some of them induce secondary tumors. Photodynamic therapy (PDT) thus appears as a promising alternative as it is nonmutagenic and generates minimal side effects. The effectiveness of PDT requires the accumulation of a photosensitizer (PS) in the tumor. However, most porphyrins are hydrophobic and aggregate in aqueous medium. Their incorporation into a nanocarrier may improve their del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 114 publications
0
15
0
Order By: Relevance
“…Assuming a minimum 100-fold dilution, this means that <1 μg of total lipid material is required for lipid analysis using this LC-MS/MS method. This is substantially less sample than that required for 1 H NMR 41 or LC-MS 11 analysis of lipid coatings (∼1 mg).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming a minimum 100-fold dilution, this means that <1 μg of total lipid material is required for lipid analysis using this LC-MS/MS method. This is substantially less sample than that required for 1 H NMR 41 or LC-MS 11 analysis of lipid coatings (∼1 mg).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this way, hydrophilic NPs can be coated with lipid bilayers, , and hydrophobic NPs can be coated with lipid monolayers. , Additionally, very small hydrophobic NPs can be encapsulated within the walls of liposomes . Lipid-coated NPs have been employed in siRNA and drug delivery, photodynamic therapy, cellular imaging, and sensing . Our group is interested in using lipid-coated lanthanide (Ln) NPs of the general formula NaLnF 4 as potential high-sensitivity mass tags for applications in mass cytometry and imaging mass cytometry (Fluidigm). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diaye et al designed a chemotherapeutic drug beta-lapachone (β-Lap) and photosensitizer m-THPC co-loaded in a different area of the biodegradable PLHNP system for the treatment of retinoblastoma malignant tumor. This hybrid carrier can be used for combined chemo-phototherapy in both oxygenated and hypoxia tumor tissues via single IV injection and concurrent phototherapy induced the expression of NQO1 in Y79 cells, offering a better therapeutic strategy for malignant tumors [ 132 ]. Another study reported improved therapeutic efficacy of combined photothermal-chemotherapy by polyaniline-lipid hybrid NPs.…”
Section: Applications Of Polymer-lipid Hybrid Nanoparticlesmentioning
confidence: 99%
“…Lipid bilayer encapsulation of NPs has been the most successful for mesoporous silica NPs , or silica-coated NPs but has also been reported for NPs composed of gold, , calcium phosphate, titanium oxide, and polymers including poly­(lactic- co -glycolic acid), , polystyrene, , and polylactic acid. We are aware of only a few examples in the literature of lipid bilayer-coated LnNPs. One should note that the lipid bilayer examples discussed here are in contrast to examples in which a monolayer of lipids forms a bilayer with the oleic acid ligands on the LnNP surface.…”
Section: Introductionmentioning
confidence: 99%